OP0156 Inhibition of structural damage with two intensive treatment strategies using infliximab or high dose intravenous steroid followed by treat to target in DMARD naÏve rheumatoid arthritis (the idea study) – a preliminary report. (23rd January 2014) - Nam, J.L.; Villeneuve, E.; Hensor, E.M.A.; Conaghan, P.G.; Keen, H.I.; Gough, A.K.; Green, M.J.; Helliwell, P.; Keenan, A.-M.; Morgan, A.W.; Quinn, M.; Reece, R.; et al.
Abstract : Background: Early intensive treatment with infliximab (IFX), high dose IV steroids and treating to target have been shown to be effective for remission induction in pts with early RA. Objectives: To compare MTX+IFX vs. MTX+high dose IV steroid as induction therapy on radiographic progression in pts with DMARD naïve RA. Methods: A 78 wk RCT of pts with early (3-12 months symptoms), DMARD naïve RA (1987 ACR criteria, DAS>2.4). Pts were randomised to 1of 2 grps:IFX or IVsteroid. Treatment was blinded to wk 26 then guided using a treat to target approach. Both grps received MTX 10mg wkly increasing to 20mg by wk 6. The IFX grp received: IFX 3mg/kg (wks 0, 2, 6, 14, 22)+dose adjustment from wk 26 according to DAS44. The IVsteroid grp received: IV methylprednisolone (MP) 250mg at wk 0, placebo infusions at wks 2, 6, 14, 22 & from wk 26 treatment escalation as follows if DAS >2.4: add SSZ+HCQ, then stop SSZ+HCQ & add LEF, then 1 of the following: MTXs/c+LEF or MTX+ciclosporin or MTX+LEF+prednisolone 5-7.5mg dly.IM MP 120mg was administered if DAS >2.4 at wks 6, 14, 22, 38, 50 & 62 for both grps. Other biologics were allowed from wk 26 per NICE guidelines. Radiographs of hands & feet done at 0, 26, 52 & 78 wks were scored using the modified Sharp-van der Heijde (vdH-S) method by 2 independent radiologists blinded to treatment grp;mean of the readers' scores was taken. Smallest detectable change was calculated to be 2 units. Results: 112 pts were randomised to MTX+IFX (n=55) or MTX+IVsteroid (n=57). Baseline mean (SD) age IFX 53.7 (13.3) vs. IVsteroid grp 53.1 (12.8); mean (SD) DAS28CRP IFX 4.2 (1.1) vs. IVsteroid 3.6 (1.1). Remission (DAS<1.6) at wk 50 was achieved in 51.9% (28/54) in the IFX & 35.7% (20/56) in the IVsteroid grp (p=0.088). Baseline median (IQR) joint space narrowing (JSN), erosion (ERO) and total vdH-S scores (TS) in the IFX (n=42) and IVsteroid (n=51) grps were: JSN 2.0 (0.0-7.5) and 1.5 (0.0-7.0), ERO 0.0 (0.0-1.6) and 0.5 (0.0-2.5), TS 3.0 (0.0-9.5) and 2.5 (0.5-9.5) respectively. At wk 52 (primary endpt), the median change in total vdH-S score was 0.0 (0.0-1.1) units in the IFX and 0.0 (0.0-2.0) units in the IVsteroid arm (p=0.157); median changes did not differ at 26 wks [IFX=0.0 (0.0-0.6) IVsteroid=0.0 (0.0-1.0), p=0.295] or 78 wks [IFX=0.0 (0.0-2.6) IVsteroid=0.5 (0.0-2.4), p=0.325]. Similar results were seen for JSN and ERO scores. Proportions of pts with radiographic non-progression (vdH-S <2.0) in the IFX and IVsteroid arms were 37/4 (88.1%) vs. 43/5 (84.3%) respectively at 26 wks (Pearson's chi-sq p=0.601); 36/42 (85.7%) vs. 39/51 (76.5%) at 52 wks (p=0.261); 31/42 (73.8%) vs. 36/51 (70.6%) at 78 wks (p=0.730). No between-grp differences were seen with non-progression defined as change≤0.5: 29/42 (69.0%) in the IFX and 29/51 (56.9%) in the IVsteroid grp (p=0.227) at 52 wks. Conclusions: In this study of DMARD naïve pts with moderate to severe RA, initial therapy with IFX+MTX and high dose IV steroid+MTX, together with tight disease control prevented radiographic progression in a significant majority of patients. Disclosure of Interest: None Declared